Life strategies doing what works, doing what matters - McGraw, Phillip C. 1950- (New York, NY Hyperion, 1999)
Tells how to analyze one's life, identify barriers to success, and take practical steps to make life more rewarding and meaningful.
ch. 1. Get real -- ch. 2. You either get it, or you don't -- ch. 3. You create your own experience -- ch. 4. People do what works -- ch. 5. You can't change what you don't acknowledge -- ch. 6. Life rewards action -- ch. 7. There is no reality; only perception -- ch. 8. Life is managed; it is not cured -- ch. 9. We teach people how to treat us -- ch. 10. There is power in forgiveness -- ch. 11. You have to name it to claim it -- ch. 12. Guided tour of your life -- ch. 13. Seven-step strategy -- ch. 14. Finding your formula.
Keywords: Change (Psychology); Success -- Psychological aspects